2020
DOI: 10.1111/tra.12729
|View full text |Cite
|
Sign up to set email alerts
|

Size‐dependent secretory protein reflux into the cytosol in association with acute endoplasmic reticulum stress

Abstract: Once secretory proteins have been targeted to the endoplasmic reticulum (ER) lumen, the proteins typically remain partitioned from the cytosol. If the secretory proteins misfold, they can be unfolded and retrotranslocated into the cytosol for destruction by the proteasome by ER-Associated protein Degradation (ERAD). Here, we report that correctly folded and targeted luminal ER fluorescent protein reporters accumulate in the cytosol during acute misfolded secretory protein stress in yeast.Photoactivation fluore… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 55 publications
(72 reference statements)
0
9
0
Order By: Relevance
“…Through the effect of ER stress, autophagy plays a protective role in a constitutive manner to enable the turnover of long-lived proteins, removal of damaged organelles, and misfolded proteins as a defense mechanism against pathogens ( Yang et al, 2016 ). When the accumulation of damaged proteins in the ER has exceeded the repair capacity of ERAD, portions of the organelle can be specifically targeted for large-scale degradation through autophagy ( Lajoie and Snapp, 2020 ). eIF2α phosphorylation induced by PERK works as a hotspot of stress-induced translation control ( Kouroku et al, 2007 ; Liu et al, 2010 ; Talloczy et al, 2002 ).…”
Section: Cross Talk Of Cell Death and Er Stressmentioning
confidence: 99%
“…Through the effect of ER stress, autophagy plays a protective role in a constitutive manner to enable the turnover of long-lived proteins, removal of damaged organelles, and misfolded proteins as a defense mechanism against pathogens ( Yang et al, 2016 ). When the accumulation of damaged proteins in the ER has exceeded the repair capacity of ERAD, portions of the organelle can be specifically targeted for large-scale degradation through autophagy ( Lajoie and Snapp, 2020 ). eIF2α phosphorylation induced by PERK works as a hotspot of stress-induced translation control ( Kouroku et al, 2007 ; Liu et al, 2010 ; Talloczy et al, 2002 ).…”
Section: Cross Talk Of Cell Death and Er Stressmentioning
confidence: 99%
“…In yeast, it was reported that ER stress caused reflux of ER proteins to the cytosol 29 , 30 . To confirm contribution of reflux of ERroGFP S4 into the cytosol to the ER reduction under proteasome inhibition, subcellular fractionation of cells was performed, resulting that most of ERroGFP S4 were localized in the ER while small portion of ERroGFP S4 were localized in the cytosol fraction (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, some ER-localized GFPs were used to demonstrate that ER stress induces some small protein relocalization into the cytosol. [141,142] By using a ratiometric redox-environment reporter GFP, relative stress-dependent GFP localization to the oxidizing environment of the ER and reducing environment of the cytosol was quantified. Increasingly, large libraries of tagged or taggable proteins are also available, increasing the throughput for measuring protein localization based on fluorescent tags.…”
Section: Confocal Microscopy To Measure Cellular Protein Localizationmentioning
confidence: 99%